Interaction of cesium adatoms with free-standing graphene and graphene-veiled SiO2 surfaces. Issue 48 (28th May 2015) - Weck, Philippe F.; Kim, Eunja; Biedermann, Grant W.
<x xml:space="preserve">Abstract</x> The interaction of Cs adatoms with mono- or bi-layered graphene (MLG and BLG), free-standing or on SiO2 substrate, was investigated using density functional theory. Smaller dipole moments created by Cs adatoms on BLG compared to MLG are predicted.